Teachers’ Questioning Strategies to Promote Students’ Engagement in EFL Classroom: The Case of Islamic Boarding Schools in Aceh - Fata, Ika Apriani; Syamaun, Arifin; Maulini, Rini; Muktabar, Fadhilah; Marhaban, Saiful; Muslem, Asnawi; Dewi, Silvi Listia (FKIP Universitas Lampung, 2022)
Teachers’ Questioning Strategies to Promote Students’ Engagement in EFL Classroom: The case of Islamic Boarding Schools in Aceh, Indonesia. Objective: The present study aims to investigate the use of questioning strategies during classroom interaction. There have been numerous studies on questioning strategies, however, Islamic boarding schools have received less attention. Method; There were N=106 students, Aged 14-16 years as students at Islamic boarding schools in Aceh, and English teachers (N=5) participated in this study selected through purposive sampling, documentation, observation, and interview are triangulation of instruments. The data were analyzed by using the descriptive qualitative form by Marzano's Observational Protocol Sheet (2013). Findings: The findings revealed that teacher mostly employs questioning strategies to check the students' knowledge and comprehension in the learning process by using many kinds of questions. Teachers used the questioning strategy through interview results to engage students and monitor the extent to which they met the learning indicators. Furthermore, when it happened to come to promoting children's critical thinking, teachers were ineffective because the questions were yes/no questions. In conclusion; it explicitly means that this strategy is interactive and effective and also can be a beneficial way to the students and teacher in the classroom interaction at school. Keywords: questioning strategies, Islamic boarding school, classroom interaction.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202207